PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP CONTINUANCE INTENTION TO USE PENGGUNA DOMPET DIGITAL DANA - Ratu Thasya Hafizhah Hidayati (Universitas Diponegoro, 2025)
Abstract: Current technological advances are a new challenge and opportunity for a company to produce innovation. The presence of digital financial services such as digital wallets is a form of innovation from companies operating in the financial sector. DANA is a digital wallet owned by PT Espay Debit Indonesia Koe. There has been a significant decline in the number of users interested in continuing to use the DANA digital wallet. This research aims to determine the influence of perceived usefulness and perceived ease of use on continuance intention to use. The type of research used is explanatory research. Sampling used non-probability techniques with purposive and incidental sampling methods. The population of this research is DANA digital wallet users in Indonesia with a sample size of 250 respondents. Data processing was carried out using SPSS ver 21 by carrying out validity tests, reliability tests, correlation coefficient tests, coefficient of determination tests, simple and multiple linear regression tests, t tests and F tests. This research shows that perceived usefulness and perceived ease of use have a positive and significant effect on continuance intention to use the DANA digital wallet, both partially and simultaneously. Keywords: perceived usefulness; perceived ease of use; continuance intention to use. Abstraksi: Kemajuan teknologi saat ini merupakan suatu tantangan dan peluang baru bagi perusahaan untuk menghasilkan inovasi. Hadirnya layanan keuangan digital seperti dompet digital merupakan bentuk inovasi dari perusahaan yang bergerak di sektor keuangan. DANA merupakan dompet digital yang dimiliki oleh PT Espay Debit Indonesia Koe. Terjadi penurunan yang signifikan pada jumlah pengguna yang berminat untuk melanjutkan penggunaan (continuance intention to use) dompet digital DANA. Penelitian ini bertujuan untuk mengetahui pengaruh perceived usefulness dan perceived ease of use terhadap continuance intention to use. Tipe penelitian yang digunakan adalah explanatory research. Pengambilan sampel menggunakan teknik non-probability dengan metode purposive dan insidental sampling. Populasi dari penelitian ini adalah pengguna dompet digital DANA di Indonesia dengan jumlah sampel sebanyak 250 responden. Pengolahan data dilakukan menggunakan SPSS ver 21 dengan melakukan uji validitas, uji reliabilitas, uji koefisien korelasi, uji koefisien determinasi, uji regresi linear sederhana dan berganda, uji t dan uji F. Penelitian ini memberikan hasil bahwa perceived usefulness dan perceived ease of use berpengaruh positif dan signfikan terhadap continuance intention to use dompet digital DANA baik secara parsial maupun simultan. Kata Kunci: perceived usefulness; perceived ease of use; continuance intention to use.